2000
DOI: 10.1128/aac.44.12.3288-3297.2000
|View full text |Cite
|
Sign up to set email alerts
|

Persistence ofChlamydia trachomatisIs Induced by Ciprofloxacin and Ofloxacin In Vitro

Abstract: An in vitro cell culture model was used to investigate the long-term effect of ciprofloxacin and ofloxacin on infection with Chlamydia trachomatis. Standard in vitro susceptibility testing clearly indicated successful suppression of chlamydial growth. To mimic better in vivo infection conditions, extended treatment with the drugs was started after infection in vitro had been well established. Incubation of such established chlamydial cultures with ciprofloxacin and ofloxacin not only failed to eradicate the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 49 publications
4
65
0
3
Order By: Relevance
“…In an in-vitro study, the persistence of C. trachomatis was demonstrated in the presence of ciprofloxacin and to a lesser extent of ofloxacin. These results reflect the clinical data that antibacterial susceptibility does not always guarantee the in-vivo success of the therapy (Dreses-Werringloer et al, 2000).…”
Section: Chlamydia and Genitourinary Tractsupporting
confidence: 60%
“…In an in-vitro study, the persistence of C. trachomatis was demonstrated in the presence of ciprofloxacin and to a lesser extent of ofloxacin. These results reflect the clinical data that antibacterial susceptibility does not always guarantee the in-vivo success of the therapy (Dreses-Werringloer et al, 2000).…”
Section: Chlamydia and Genitourinary Tractsupporting
confidence: 60%
“…Conversely, ciprofloxacin and ofloxacin have shown to be not eradicating the organism from host cells in vitro, but rather to induce a state of Chlamydia persistence characterized by the presence of noncultivable, but fully viable bacteria and the development of aberrant inclusions [9]. Despite this, however, the association of both compounds has been effective in eradicating C. trachomatis Hsp-60 cDNA in clinical specimens as demonstrated by RT-PCR [99].…”
Section: Discussionmentioning
confidence: 96%
“…In vitro studies have shown that several factors including nutrient depletion, cytokines (INF-γ), iron restriction, amino acids, Ca++, and certain antibiotics can induce the Chlamydial persistent stage [9,41,42]. In particular IFN-γ directly inhibits bacterial growth [43] and induces Chlamydia persistence by allowing 60 and 12 kDa cystein protein inhibition and tryptophan depletion which can stop the expression of late proteins such as major outer membrane protein (MOMP) that in turn stop the progress of RB division and RB conversion into EBs leading to aberrant Chlamydial RBs [41,44].…”
Section: Pathogenesis Of Chlamydia Persistence and Chronic Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of Chlamydia is a part of vital cycle of these microorganisms, it can be easily reproduced in cell culture under the effects of some factors, including AB [4]. Azithromycin, ciprofloxacin, and ofloxacin are inductors of Chlamydia persistence, they interrupt the productive intracellular cycle of Chlamydia, the microorganisms stop active multiplication, but retain metabolic activity, which is seen from negative result of cultural study and detection of short-living rRNA transcripts [3,4].…”
Section: Resultsmentioning
confidence: 99%